Efeito imunomodulador e antimicrobiano dos extratos de Lippia alnifolia e Vatairea macrocarpa na periodontite - Barreto Neto, Laerte Oliveira (2019)
The use of herbal medicines has become a valuable resource in its treatment of oral disorders such as fungal and bacterial infections. One of the most prevalent infectious and inflammatory diseases in the mouth is periodontitis, which if left untreated, can lead to tooth loss. This study evaluated the immunomodulatory and antimicrobial potential of Lippia alnifolia Mart & Schauer (LA) and Vatairea macrocarpa (Benth.) Ducke (VM) leaf extract. Immunological evaluation was performed by immunoassay after culturing peripheral blood cells of individuals with and without periodontitis with the plant extract and the periodontopathogen Porphyromonas gingivalis (PG) extract. Antimicrobial activity was tested with minimal inhibitory concentration and disk diffusion assay. LA extract inhibited the production of IL-13, IL-6 and IFN-γ, both in relation to the basal concentration produced by cells and the concentration produced by cells co-cultured with PG extract. Co-cultivation of MV with PG promoted a reduction in IL-1β, IL-13, IL-6, IFN-γ, IL-10 and IL-17 levels. The LA extract showed bacteriostatic activity for Bacillus subtilis, Escherichia coli, Micrococcus luteus, Pseudomonas aeruginosa, Staphylococcus aureus and Salmonella choleraesuis, fungistatic for Candida albicans and fungicide for Candida glabrata. VM showed bactericidal activity for Micrococcus luteus species and bacteriostatic other bacteria, as well as fungistatic activity for Candida albicans and fungicide for Candida glabrata. LA and VM extracts are promising in regulating cytokine production in PG antigens and in controlling oral microorganisms.